Low plasma glutamine in combination with high glutamate levels indicate risk for loss of body cell mass in healthy individuals: the effect of N-acetyl-cysteine - Kinscherf, Ralf; Hack, Volker; Fischbach, Thomas; Friedmann-Bette, Birgit; Weiß, Christel; Edler, Lutz; Bärtsch, Peter; Dröge, Wulf (Journal of molecular medicine, 1996)
Skeletal muscle catabolism, low plasma glutamine, and high venous glutamate levels are common among patients with cancer or human immunodeficiency virus infection. In addition, a high glycolytic activity is commonly found in muscle tissue of cachectic cancer patients, suggesting insufficient mitochondrial energy metabolism. We therefore investigated (a) whether an “anaerobic physical exercise” program causes similar changes in plasma amino acid levels, and (b) whether low plasma glutamine or high glutamate levels are risk factors for loss of body cell mass (BCM) in healthy human subjects, i.e., in the absence of a tumor or virus infection. Longitudinal measurements from healthy subjects over longer periods suggest that the age-related loss of BCM occur mainly during episodes with high venous glutamate levels, indicative of decreased muscular transport activity for glutamate. A significant increase in venous glutamate levels from 25 to about 40 μM was seen after a program of “anaerobic physical exercise.” This was associated with changes in T lymphocyte numbers. Under these conditions persons with low baseline levels of plasma glutamine, arginine, and cystine levels also showed a loss of BCM. This loss of BCM was correlated not only with the amino acid levels at baseline examination, but also with an increase in plasma glutamine, arginine, and cystine levels during the observation period, suggesting that a loss of BCM in healthy individuals terminates itself by adjusting these amino acids to higher levels that stabilize BCM. To test a possible regulatory role of cysteine in this context we determined the effect of N-acetyl-cysteine on BCM in a group of subjects with relatively low glutamine levels. The placebo group of this study showed a loss of BCM and an increase in body fat, suggesting that body protein had been converted into other forms of chemical energy. The decrease in mean BCM/body fat ratios was prevented by N-acetyl-cysteine, indicating that cysteine indeed plays a regulatory role in the physiological control of BCM.
Gesehen am 17.01.2024